O Instituto Inhotim na sensibilização ambiental: contribuições das visitas mediadas panorâmicas para a educação ambiental - Jungers, Maria Luiza Carlette (2015)
Environmental awareness is an indispensable condition in educational work focused on the care related to the environment and indispensable in the formation of citizens for an environmentally sustainable society. Starting from the assumption that the Inhotim Institute offers the community art and environmental education activities, the research aimed to: know the origin and history of the Inhotim Institute and analyze the contributions of the mediated panoramic visits conducted by environmental and art educators of the Institute, aimed at visitors regarding to environmental awareness. The Institute houses a contemporary art museum and a botanical collection of rare beauty, where actions as well as cultural, artistic and environmental education activities are developed, which offer the community at large, students and teachers a rich space in non-formal teaching-learning related to the environment. Its founder Bernardo de Mello Paz completely transformed his private property, where was in an intense highly polluting mining work, in a cultural space for contemporary art in the midst of unspoiled nature. He demonstrated thus be possible to revitalize the cultural and natural heritage of an area that was previously degraded by man. It was established by the discourse of the interviewed visitors that the work of the environmental educators is carried out with responsibility and respect for others, highlighting interdisciplinary. Regarding mediated environmental education visits, it was evident, that program provides to visitors - students, teachers and the general public - fun and educational experiences that can collaborate with the teaching-learning process, and thus achieve the environmental awareness.